Competition policy for health care provision in France - Choné, Philippe (Health policy (Amsterdam), 2017)
•More than two thousand public and private hospitals operate in France.•Government reports argue that activity-based payment and competition impede synergies between hospitals.•An important reform coming into effect in January 2016 mandates close cooperation between public hospitals.•GP fees are set nationally while many self-employed specialist physicians may overcharge.•Government regulation and centralized negotiations tend to be favoured over market mechanisms. There are more than two thousand hospitals in France, about equally divided between government-owned and privately-owned hospitals. Activity-based payment, which has been generalized in 2008 for acute care hospitals, has raised competition issues as DRG tariffs differ according to ownership status. Furthermore, the payment rule has been criticized for preventing the realization of potential hospital synergies, and as a result a recent reform has mandated close cooperation between public hospitals. The physician market is dual, with most GPs being subject to fee regulation and many self-employed, private-practice, specialist doctors being allowed to set their prices freely. Government regulation and centralized negotiations have traditionally been preferred to market mechanisms in this industry.